RAMP2-AS1 Regulates Endothelial Homeostasis and Aging - Lai, Chih-Hung; Chen, Aleysha T.; Burns, Andrew B.; Sriram, Kiran; Luo, Yingjun; Tang, Xiaofang; Branciamore, Sergio; O’Meally, Denis; Chang, Szu-Ling; Huang, Po-Hsun; Shyy, John Y-J.; Chien, Shu; et al. (Frontiers in Cell and Developmental Biology, 2021)
The homeostasis of vascular endothelium is crucial for cardiovascular health and endothelial cell (EC) aging and dysfunction could negatively impact vascular function. Leveraging transcriptome profiles from ECs subjected to various stimuli, including time-series data obtained from ECs under physiological pulsatile flow versus pathophysiological oscillatory flow, we performed principal component analysis (PCA) to identify key genes contributing to divergent transcriptional states of ECs. Through bioinformatics analysis, we identified that a long non-coding RNA (lncRNA) RAMP2-AS1 encoded on the antisense of RAMP2, a determinant of endothelial homeostasis and vascular integrity, is a novel regulator essential for EC homeostasis and function. Knockdown of RAMP2-AS1 suppressed RAMP2 expression and caused EC functional changes promoting aging, including impaired angiogenesis and increased senescence. Our study demonstrates an integrative approach to quantifying EC aging based on transcriptome changes, which also identified a number of novel regulators, including protein-coding genes and many lncRNAs involved EC functional modulation, exemplified by RAMP2-AS1.